TIPOLOGI BANGUNAN PAIKHONG SEBAGAI LANDMARK KOTA SINGKAWANG KALIMANTAN BARAT - Rimba, Cornellia; Widaningsih, Lilis (TERAS)
The cities majority in the world especially big cities are have unique character that is to be identity. Dominant building is one of identity of place or city. This building is built for purpose particularly and so are having more qualitative and quantitative value. However the dominant building gives influence to place or object in the neighborhood. In the visual, dominant building or architecture element can be landmark as interesting focus point and contrast on the place and environment. For the city or region, landmark is external element and dominant visual form such as mountain, sky rapper building, high tower, ritual religiosity building and etc. So landmark can be orientation point that helping people for know to place. The Paikhong building existent as place of ritual religiosity at Singkawang city is identity character on urban morphology that having majority population is china people. Almost all of the region with the china people majority such as Singkawang Barat and Singkawang Selatan are found Phaikong building actually. In the general, Paikhong is built at the cross street side and should be identity image of city with china majority inhabitant.Â Key word: architecture identity, landmark, image of city, typology, morphology.